Integrating Sharia Literacy and Digital Philanthropy Amidst the FoMO Phenomenon - Amry Abdurrahman; M. Kholid; Ulya Dharodjah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The era of financial digitalization triggers behavioral pathologies among Muslim Generation Z through Fear of Missing Out (FoMO), driving impulsive consumption (israf). While existing literature narrowly positions Sharia financial literacy as a passive, theoretical cognitive instrument, this study aims to conceptualize the active moderating roles of Sharia financial literacy and digital philanthropy in mitigating these algorithm-driven distortions. Employing a Qualitative Systematic Literature Review (SLR) via the PRISMA protocol, 24 peer-reviewed articles (2019–2025) were analyzed from Google Scholar, Crossref, and Dimensions using Publish or Perish. The primary novelty of this study lies in its theoretical synthesis, introducing the "Transcendental Moral Filter Ecosystem". This innovative model restructures the expanded Theory of Planned Behavior (TPB) by integrating transcendental accountability (Hifdz al-Mal within the Maqasid Sharia framework) as an active value anchor. The findings demonstrate that cyber-based Sharia literacy acts as a dynamic moral filter, reorienting FoMO-driven positional consumption into productive economic decisions through digital philanthropy optimization (Ziswaf). This study offers a vital structural framework for academics and regulators in formulating Islamic financial education strategies resilient to modern cyber pathologies.